2021
DOI: 10.1021/acsmacrolett.1c00503
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nanorod Physical Roughness on the Aggregation and Percolation of Nanorods in Polymer Nanocomposites

Abstract: Using molecular dynamics simulations, we elucidate the effect of nanorod roughness on nanorod aggregation, dispersion, and percolation in polymer nanocomposites (PNCs). By choosing coarse-grained models that enable systematic variation of the nanorod roughness and by selecting purely repulsive pairwise interactions for nanorods and polymer chains, we show how nanorod roughness affects the entropic driving forces for various PNC morphologies. At this entropically driven limit, we find that increasing nanorod ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 58 publications
1
5
0
Order By: Relevance
“…Recently, it has been shown that the organization of nanorods in polymer nanocomposites depends on the details of the nanorod model. 49,50 For the specific models of nanorods and polymers used here and the low volume fraction of nanorods in the simulations, we have confirmed that the nanorods are well dispersed without any aggregation in all samples. 43 Additionally, because of the low volume fraction of nanorods in the simulations and the lack of a theory for the long-range correlation of nanorod pairs, we do not attempt to quantify and correct for the effects of any long-range pair correlation on the dynamics of individual nanorods.…”
Section: Models and Methodssupporting
confidence: 62%
“…Recently, it has been shown that the organization of nanorods in polymer nanocomposites depends on the details of the nanorod model. 49,50 For the specific models of nanorods and polymers used here and the low volume fraction of nanorods in the simulations, we have confirmed that the nanorods are well dispersed without any aggregation in all samples. 43 Additionally, because of the low volume fraction of nanorods in the simulations and the lack of a theory for the long-range correlation of nanorod pairs, we do not attempt to quantify and correct for the effects of any long-range pair correlation on the dynamics of individual nanorods.…”
Section: Models and Methodssupporting
confidence: 62%
“…Other than the rod thickness, the diffusion of a nanorod is anticipated to depend on the surface roughness of the nanorod. Molecular simulations have demonstrated the effects of surface roughness on the phase behavior of thin nanorods in polymers 168 and may reveal the effects of surface roughness on the dynamics of thin nanorods as well. Further extension of the research on nanorods in polymer melts may include the flexibility of the nanorod.…”
Section: Dynamics Of Thin Nanorods In Polymer Melts� Effects Of Aniso...mentioning
confidence: 99%
“…Nanorod fillers in polymer matrices offer unique advantages over spherical fillers due to their enhanced optical, electrical, and mechanical properties . While there have been recent advances in understanding the dispersion and aggregation of nanorods in unentangled , and entangled polymer matrices, less is known about the factors governing the dynamics of polymer nanocomposites with nanorod fillers. Understanding the structure and dynamics of nanorods is key to tailoring their properties for applications such as nanorheology, drug delivery, , and mechanical reinforcement of polymer matrices …”
Section: Introductionmentioning
confidence: 99%